44 Evaluation of Prenatal Transportation Stress on Humoral and Cell-Mediated Immunity After Modified-Live Viral BVDV Vaccination in Brahman Calves. (21st September 2022) - Earnhardt, Audrey L; Wellman, Catherine L; Falkenberg, Shollie M; Long, Charles R; Randel, Ron D; Welsh, Thomas H
Abstract: The objective of this study was to evaluate whether prenatal transportation stress (PNS) affects the immune response of Brahman calves after vaccination against Bovine Viral Diarrhea Virus (BVDV). Mature Brahman cows inseminated to a single Brahman sire in 2018 were assigned to either Control (n=35; not transported) or PNS (n=37; 2h of transportation at 60, 80, 100, 120, and 140±5 d of gestation). Of the calves born in 2019, 11 Control and 12 PNS calves were studied for vaccine treatment (VAX). Temperament score, body weight, and blood samples were obtained from calves prior to weaning (D-28), prior to first BoviShield vaccine (D+35), and after second BoviShield vaccine (D+98). Serum cortisol was determined by RIA. Humoral immune response was evaluated by virus neutralization (VN) assays using serum collected at respective timepoints post-vaccination. Cell-mediated immune (CMI) response was evaluated using a novel PrimeFlow RNA assay that incorporates cell surface marker staining with intracellular RNA expression of cytokines on blood samples obtained at D+35 and D+98. Data were analyzed using GLM procedures of SAS. Only total WBC and absolute lymphocytes were increased with PNS (P< 0.05), while lymphocytes were also decreased with VAX (P< 0.05). There was no PNS effect on the VN or CMI results, serum cortisol concentration, or temperament score. VAX tended (P=0.06) to reduce serum cortisol, as well as resulted in an increase in VN titers (P< 0.01) and frequency of interferon-γ mRNA expression in the CD4 + population (P< 0.01), but not in CD25 + population (P=0.26). Interaction between sampling day and VAX resulted in more drastic increase (P< 0.05) from D+35 to D+98 in VN titers, CD4 + population frequency of interferon-γ mRNA expression, and CD25 + population mean fluorescent intensity. Vaccine treatment positively affected humoral and cell-mediated immune responses; however prenatal transportation stress did not negatively impact response of Brahman calves to immunization against BVDV.